Towards integrated wind farm control: Interfacing farm flow and power plant controls. Issue 2 (29th May 2022) - Kölle, Konstanze; Göçmen, Tuhfe; Garcia‐Rosa, Paula B.; Petrović, Vlaho; Eguinoa, Irene; Vrana, Til Kristian; Long, Qian; Pettas, Vasilis; Anand, Abhinav; Barlas, Thanasis K.; Cutululis, Nicolaos; Manjock, Andreas; et al.
Abstract: Concepts for control of wind farms (WFs) can be clustered into two distinct concepts, namely, wind power plant control (WPPC) and wind farm flow control (WFFC). WPPC is concerned with the connection to the power system, compliance with grid codes, and provision of power system services. This comprises the traditional way of operating a WF without consideration of aerodynamic turbine interaction. However, flow phenomena like wake effects can have a large impact on the overall performance of the WF. WFFC considers such aerodynamic phenomena in the WF operation. It can be viewed as a new feature that shall be integrated with the existing control functions. The interaction of these different control concepts is discussed in this article, leading to an identification of the challenges whose solutions will contribute to a successful integration of electrical system and aerodynamic aspects of WF control. Abstract : Wind power plant control (WPPC) and wind farm flow control (WFFC) aretwo distinct concepts to control wind farms. Traditionally, WPPC is concernedwith the connection to the power system, compliance with grid codes, andprovision of power system services. WFFC considers aerodynamic turbineinteractions like wake effects. This article discusses the interaction of theseconcepts, leading to an identification of challenges whose solutions willcontribute to a successful integration of electrical system and aerodynamicaspects of wind farm control.